Kerajaan dan Kesultanan Dunia Melayu: Kasus Sumatra dan Semenanjung Malaysia - Suwardi Mohammad Samin (Criksetra: Jurnal Pendidikan Sejarah, 2015)
Study canopy above is the result of the investigation and writing in 2012 and passed in 2013 that the results have been a dummy book "Overseas from Sumatra to Peninsular Malaysia". Naming kingdom lasted about a century to 7 M 13M is the Hindu and Buddhist, such as the Royal Malay Jambi, Dharmasyraya, Sriwijaya, Minangkabau, in Riau as Kandis, Kritang, Ghasib, and so on. Since the entry and development of Islam in Sumatra and the peninsula called the empire, such as: the Sultanate of Pasai Ocean, Barus, Deli, shavings, Langkat, Siak Sri Indrapura, Indragiri, Rokan, and so on. Sementra it grows Peninsula Peninsula border with the kingdom of Siam, known as Ligor inscription mentions as Situmarat, Langkasuka, and after the Islamic sultanate of Malacca, Johor, Kedah, Perak, Pahang, Selangor, Negeri Sembilan, Terengganu, Kelantan, Perlis. Archaeological evidence and sources manuskrips and books become a source of study. From the study was appointed sub-headline: "Diaspora" secaratimbal-balikantara Sumatra and Peninsular Malaysia. Analysis and Interpretation was a common thread of this discussion and at the end of a few grains obtained conclusions and suggestions